Studi Kasus Gaya Kepemimpinan Kepala Sekolah dalam Pelaksanaan Supervisi Pendidikan - Ahmad Hariyanto; Dwi Ira Puspita; Merintan Merintan; Nabila Astriani; Krisfalesi Krisfalesi; Yuniar Pratiwi; Zakiyul Fikri; Samsilayurni Samsilayurni (Journal of Innovation in Teaching and Instructional Media, 2026)
This study analyzes the principal’s leadership style in supervising and wants to know how the results are in improving teacher performance. This study uses a qualitative method with a case study approach. The results of the study showed that school principals applied a democratic leadership style in the implementation of educational supervision, with open communication, continuous coaching, and feedback to teachers. The novelty of this research lies in an in-depth presentation of the leadership practices of school principals in educational supervision which is analyzed contextually through a qualitative approach. The implication of the research is that the application of democratic leadership styles in educational supervision has an important role in building a school climate. This research makes a theoretical and practical contribution to the development of education management and the improvement of learning quality.